Seroprevalence of SARS-CoV-2 and assessment of epidemiologic determinants in Portuguese municipal workers - Nuno Manuel Barbosa de Barros Ferreira (2021)
Abstract Objectives: To assess the presence of SARS-CoV-2 antibodies in municipal employees of Northern Portugal during the first pandemic wave (May-June 2020) and its association with epidemiologic and clinical variables. Design: Cross-sectional study. Setting: Municipal employees of two cities in Northern Portugal. Participants: 1696 participants were assessed and completed the study, of whom 1256 were males. Participants ages ranged from 18 to 70 years old. Primary and secondary outcome measures: The primary outcome consisted of the proportion of individuals presenting antibodies to SARS-CoV-2 as assessed by serological tests. We also applied an epidemiological survey to evaluate the association between positive serological test results and epidemiologic variables and clinical presentations. Reported symptoms were evaluated on their sensitivity, specificity, and predictive values. Results: The frequency of SARS-CoV-2 was 2.9% (95% confidence interval [CI]=2.1-3.7%). We observed no significant differences between different occupation groups, with similar antibody frequencies among those who were and those who were not in direct contact with COVID-19 patients in their professional activity (3.9% versus 2.7%, respectively; OR=1.5; 95%CI=0.8-2.8; p=0.222). The highest risk of infection was associated with the presence of a confirmed COVID-19 case in the household (OR=17.4; 95%CI=8.3-36.8; p<0.001) while living with a healthcare professional did not associate with a higher risk of infection (OR=1.0; 95%CI=0.4-2.5; p=0.934). Anosmia/dysgeusia was the symptom with the highest positive predictive value (52.2%; 95%CI=31.8-72.6%; p<0.001) and specificity (99.3%; 95%CI=98.9-99.7%; p<0.001), and cough was the most prevalent symptom among SARS-CoV-2 seropositive participants (36%). Conclusion: We observed a SARS-CoV-2 seroprevalence of 2.9% amongst the participants, with similar results between different occupation groups. Anosmia/dysgeusia had the highest positive predictive value and specificity among the assessed symptoms.